Ideologi Welfare State Konstitusi: Hak Menguasai Negara Atas Barang Tambang - Marilang Marilang (The Constitutional Court of the Republic of Indonesia, 2012)
Failures indicated by countries with individualistic capitalist liberal ideology (the classical rule of law state) and those with socialist ideology spawned welfare state ideology that seeks to combine the principles of the rule of law with the principles of the socialist state which adopts the ideology that the state no longer functions as simply an instrument of power but is seen as a tool of service (an agency of service) in the form of policy-making, making arrangements, administration, management and supervision of mining products. Welfare state ideology is adopted by our constitution, so that the mandate of the 1945 Constitution, Article 33 paragraph (3) to the statewhich becomes the main tasks of the government in managing mining goods opens wide opportunities to realize maximum benefit for the people.